A new indicator to implement effective spending review policies in the public procurement for standardized goods - Adriano de Leverano; Susmita Baulia (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2023)
We suggest an alternative indicator that can lead to price reductions in the public procurement market for goods, i.e., the elasticity of prices to quantities purchased. We apply the analysis to the procurement of medical devices by exploiting a survey from the Italian AntiCorruption Authority. The data report for each contract and a series of buyers across the country: a) the quantities, b) the unitary price for the devices, and c) the characteristics of the devices. We find that our measure could provide savings equal to about 17% of the total expenses.
Keywords: H51; H57; H75; I18; 330; Public procurement; Medical devices; Spending review